Teachers and students, reflections on learning in near and Middle Eastern cultures: collected studies in honour of Sebastian Günther - Pielow, Dorothee; Newiger, Jana; Jamouhi, Yassir el (Islamic history and civilization, 2024)
"Teachers and Students: Reflections on Learning in Near and Middle Eastern Cultures. Collected Studies in Honour of Sebastian Günther contains essays on the developments, ideals, and practices of teaching and learning in the Islamicate world, past and present. The authors address topics that reflect - and thus honour - Sebastian Günther's academic achievements in this particular area. The volume offers fresh insights into key issues related to education and human development, including their shared characteristics as well as their influence on and interdependence with cultures of the Islamicate world, especially in the classical period of Islam (9th-15th century CE). The diverse spectrum of topics covered in the book, as well as the wide range of innovative interdisciplinary approaches and research tools employed, pay tribute to Sebastian Günther's research focus on Islamic education and ethics, through which he has inspired many of his students, colleagues, and friends"--